CULTUROLOGICAL APPROACH IN THE FORMATION CONTENTS OF THE PEDAGOGICAL TRAINING OF THE FUTURE TEACHER AT A CLASSICAL UNIVERSITY - H.B. Shtelmakh (Academy of Cognitive and Natural Sciences, 2003)
No abstract.